Teaching Listening Using Informational Technologies - Turdiyeva Nilufar Yokubovna; Mingboyeva Dilfuza Olim qizi (Scientific Trends, 2024)
The article examines the process of teaching students to listen with special attention to the methodology of rational use of Information Technology in teaching listening in English.
Keywords: Listening, information technology, perceptual mental, mnemic activity, authentic texts, socio-cultural component, communicative competence, audiobook, listening, adapted.